Pengaruh Kombinasi Pijat Punggung Dan Dzikir Terhadap Tingkat Stres Pada Penderita Hipertensi - Rudi Haryono; Iman Permana; Nur Chayati (Jurnal Keperawatan Notokusumo, 2016)
Background : The World Health Organization (WHO) in 2012 released that 26,4 % of world population suffer from hypertension. One of the contributory factors to blood pressure is stress. The level of blood pressure can be reduced by lowering down the stress level. A non-pharmacology effort to decrease stress level is through relaxation techniques such as back massage and dhikr. Objective : The aim of this research was to reveal the influence of back massage and dhikr to the level of stress of hypertensive patient. Method : This research applied quasi experiment design by using pretest-posttest intervention with control group. The samples of this research were 60 respondents divided to 30 respondents as intervention group and 30 respondents as control group. The intervention group given was a back massage and dhikr as well as anti-hypertension therapy for 3 days consecutively while the control group was only given anti-hypertension therapy. Mann-Whitney test was used to analyze the influence of combination therapy. Result : Test normality using Shapiro Wilk with p=0,012, which means the data is not normally distributed.Wilcoxon test for the influence of the intervention group with p value of 0,008. Back massage and dhikr was proven to decrease the level of stress (p=0,011) by Mann Whitney test in two groups. Conclusion : Back massage and dhikr was proven to significant decrease the level of stress. Decrease stress that occurs is a positive effect of the combination of relaxation . In the next step is expected to decrease stress will affect also to a decrease in blood pressure in patients with hypertension.